KAJIAN PENGGUNAAN RUMPUT LAUT (Eucheuma cottonii) SEBAGAI BAHAN TAMBAHAN DALAM PENGOLAHAN KAMABOKO IKAN PATIN (Pangasius hypopthalmus) - Hidayat, Nasrul; Ilza, Mirna; Syahrul, Syahrul (Fakultas Perikanan dan Kelautan Universitas Riau, 2014)
The aim of this study was to determine the consumer acceptance of catfish kama-boko with the addition of seaweed. A total of 10 kg catfish was obtained from one ofmarket in Pekanbaru city was processed into kamaboko. Four types of kamaboko weremade from catfish meat, corn starch, salt, onion, garlic, pepper and each of treatmentwas fortified with seaweed 0%, 5%, 10% and 15%. Parameters was observed on con-sumers acceptance and proximat analysis. The result showed that the catfish kamabokofortified with seaweed 15% was the best treatment and preferred by consumers with3.71% of organoleptik value, 70.41% of water content, 27.52% of protein, 2.79% ofash content, 2.99% of fat and 2.92% of crude fiber.